Linking leadership to learning: how instructional and distributed leadership shape teacher development and school outcomes - Elly Pitriani; Manap Somantri; Muhammad Kristiawan (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This systematic literature review examines the relationship between educational leadership and school performance, with a focus on the mediating role of teacher professional development. Following PRISMA 2020 guidelines, a systematic search of Google Scholar and PubMed databases was conducted for peer-reviewed articles published between 2020 and 2024. Of 347 initially identified records, 25 studies met predetermined inclusion criteria (empirical research, focus on K-12 school leadership, reported outcomes related to school performance or teacher development). Results indicate that three leadership models dominate the literature: instructional leadership (reported in 64% of studies), distributed leadership (48%), and transformational leadership (52%). All 25 studies reported positive associations between at least one leadership model and school performance. Instructional leadership demonstrated the most consistent positive associations with teacher self-efficacy (effect sizes ranging from β = 0,31 to 0,58) and student outcomes. Distributed leadership was most strongly associated with teacher job satisfaction and professional agency. Transformational leadership showed indirect effects on school performance mediated through organizational culture and teacher commitment. The Professional Learning Community (PLC) framework emerged as a key structural mechanism integrating these leadership approaches. Limitations include potential publication bias, predominance of cross-sectional qualitative designs, and limited geographical diversity (72% of studies from Western or East Asian contexts). This review provides a synthesized framework for understanding how different leadership models operate through teacher professional development to affect school performance, with implications for principal preparation and school improvement policy.